THE INFLUENCE OF MATERNAL KETONURIAON BIOPHYSICAL FETAL TEST RESULTS IN THE EVALUATION OF POSTTERM PREGNANCY (Iraqi Journal of Medical Sciences, 2016)
Background:The perinatal morbidity and mortality increase significantly as pregnancy progresses beyond term. The ketone production as a result of dehydration becomes significant in the latter portion of pregnancy.Objective:To determine whether ketonuria, a commonly assessed urinary marker of maternal starvation and dehydration, is associated with abnormal fetal test results in the setting of postterm pregnancy.Methods: During a one-year period (March 2007-March 2008), a total of 180 visits of 100 patients of postterm pregnancies (? 41 weeks’ gestation) occurred at Baghdad Teaching Hospital. Maternal assessment included vital signs and urinalysis. The presence and degree of maternal ketonuria was correlated against abnormal results of fetal heart rate tests, non stress tests, amniotic fluid index measurements (the biophysical profile scores) performed on the same day.Results:There were 180 evaluations suitable for inclusion in the study. Clinically detectable ketonuria occurred in 13.9% of the patients studied. Patients with clinically detectable ketonuria were at increased risk relative to patients without ketonuria for abnormal outcomes during postterm testing, including the presence of oligohydramnios (28% vs. 9.7%; p
Keywords: maternal ketonuria biophysical fetal test postterm pregnancy